Improving Social Welfare: Evaluation of Minimum Service Standards In Gorontalo Province - Soedjono Adam, Erfirmansyah; Tahir, Arifin; Abdussamad, Zuchri; Hamim, Udin; Aneta, Yanti (IJESS International Journal of Education and Social Science, 2024)
This study evaluates the implementation of Minimum Service Standards (SPM) in the social sector in Gorontalo Province, which aims to improve the welfare of vulnerable communities such as people with disabilities, neglected children, and the elderly. A descriptive-qualitative approach is used to analyze target achievement, service facilities, human resource (HR) capacity, and cooperation between stakeholders.The results of the study show an increase in SPM achievement from 55.46% in 2022 to 70.30% in 2023. However, service facilities and HR competencies still need improvement. Cross-sectoral collaboration helps overcome obstacles, but is not yet fully optimal. Opportunities for improvement include service digitalization, HR training, and strengthening partnerships. Strategic recommendations include increasing the budget, developing a policy roadmap, and public education campaigns. These steps are expected to encourage the achievement of more effective SPM to improve social welfare in Gorontalo.